1989
DOI: 10.1164/ajrccm/139.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Morphine on Breathlessness and Exercise Tolerance in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Previous studies have shown that opiates increase the maximal external work performed at exhaustion in patients with chronic obstructive pulmonary disease (COPD). The mechanism responsible for this improvement in exercise tolerance is unknown. The purpose of this study was to determine the effects of an oral morphine solution (0.8 mg/kg) on the exercise tolerance, perception of dyspnea, and arterial blood gases of patients with COPD. Thirteen eucapnic patients with stable COPD (FEV1 = 0.99 +/- 0.48) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
3
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(77 citation statements)
references
References 8 publications
5
66
3
3
Order By: Relevance
“…Several conditions have been shown to alter separately the D/VE and the VE/VCO 2 slopes. Acute oral morphine ingestion in COPD patients reduces the D/VE slope without affecting the VE/VCO 2 slope [24] whilst in patients with chronic hyperthyro茂dism the VE/VCO 2 slope is increased and the D/VE slope is normal [25]. The absence of correlation between the two slopes in the present study is consistent with these findings, and provides further evidence that dyspnoea experienced by patients with COPD is a sensation quite different from a simple awareness of an increase in ventilation [7,26].…”
Section: Discussionmentioning
confidence: 93%
“…Several conditions have been shown to alter separately the D/VE and the VE/VCO 2 slopes. Acute oral morphine ingestion in COPD patients reduces the D/VE slope without affecting the VE/VCO 2 slope [24] whilst in patients with chronic hyperthyro茂dism the VE/VCO 2 slope is increased and the D/VE slope is normal [25]. The absence of correlation between the two slopes in the present study is consistent with these findings, and provides further evidence that dyspnoea experienced by patients with COPD is a sensation quite different from a simple awareness of an increase in ventilation [7,26].…”
Section: Discussionmentioning
confidence: 93%
“…In two studies published in the 1980s, a decrease in exercise-induced dyspnoea was obtained in COPD subjects following oral administration of either 15 mg dihydrocodeine [1], or 0.8 mg路kg -1 of a morphine solution [2]. However, serious side-effects occurred in the latter study.…”
Section: Discussionmentioning
confidence: 95%
“…Systemic treatment with opioids has been reported to reduce dyspnoea in some patients groups [1,2], but adverse effects are common and preclude their long-term use. Nebulized morphine is potentially attractive, since it is free of the adverse effects associated with systemic therapy and uncontrolled studies have suggested a beneficial effect on dyspnoea [3,4].…”
mentioning
confidence: 99%
“…Treatment of breathlessness is most effective when the primary cause can be identified and modified, but in those conditions in which treatment currently has little to offer, it is logical to explore the feasibility of modifying the perception of breathlessness in order to relieve distress. Many drugs, such as hydrocodeine [52][53][54][55], morphine [56][57][58][59], diazepam [60][61][62][63] and promethazine [62,63], have been tested for their ability to relieve intractable breathlessness, with inconclusive results. Relief when obtained can, in most cases, be adequately explained by a reduction in respiratory work without the need to postulate any alteration in the perceptive mechanism or ability.…”
Section: The Use Of Drugs To Alter the Perception Of Breathlessnessmentioning
confidence: 99%
“…Using oral morphine (0.8 mg路kg -1 ) in patients with severe chronic airflow obstruction, LIGHT et al [58] have shown that exercise endurance was increased and breathlessness, assessed using a modified Borg scale, significantly decreased following oral morphine treatment. The reduction in breathlessness in this study was achieved at the expense of an increase in arterial carbon dioxide tension, a reduction in ventilatory drive (P 0.1 ), and was thought by the authors to be due to a combination of lowered ventilatory requirements for a given workload and also to altered perception.…”
Section: The Use Of Drugs To Alter the Perception Of Breathlessnessmentioning
confidence: 99%